Influence of Dielectric Constants of Dioxane-Water Mixture on Formation Constants of Cu(II)-Glycyl-Glycyl-Glycine Complexes - Chachere, S.D.; Sondawale, P.J.; Narwade, M.L. (Asian Journal of Chemistry, 2010)
The interaction between Cu(II) complexes with glycyl-glycylglycine in different percentages of dioxane-water mixture at 0.1 M ionic strength and at 27 ± 0.1 °C has been studied potentiometrically. The method of Bjerrum and Calvin, as modified by Irving and Rossotti, has been used in the present work. The data obtained can be used to study the values of proton-ligand and metal-ligand stability constants for 1 : 1 and 1 : 2 complexes. It showed that proton-ligand and metal-ligand stability constants increase with increasing the percentage of dioxane-water mixtures.